2007
DOI: 10.1007/s12010-007-9212-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of biodegradation of synthetic plastic and foams

Abstract: Synthetic polymeric foams have pervaded every aspect of modern life. Although foams provide numerous benefits, they also cause a significant environmental litter problem because of their recalcitrant and xenobiotic nature. Biodegradation may provide solution to the problem, but not enough is known about the biodegradation process of synthetic plastic and plasticbased foams. This review has been written to provide an overview of the current state of plastic foam biodegradation. Several biodegradation pathways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(85 citation statements)
references
References 64 publications
1
76
0
3
Order By: Relevance
“…Further BLAST analysis of the actin and translation elongation factor 1␣ partial sequences from these six strains showed the highest matches with the following species: T1.PL.1 with Cladosporium pseudocladosporioides, A2.PP.5 and A3.I.1 with Cladosporium tenuissimum, BP8.I. 3 …”
Section: Isolation Of Fungimentioning
confidence: 95%
“…Further BLAST analysis of the actin and translation elongation factor 1␣ partial sequences from these six strains showed the highest matches with the following species: T1.PL.1 with Cladosporium pseudocladosporioides, A2.PP.5 and A3.I.1 with Cladosporium tenuissimum, BP8.I. 3 …”
Section: Isolation Of Fungimentioning
confidence: 95%
“…Polymeric foams are difficult to transport and recycle because of their low densities and bulky volumes. Gautam et al (2007) studied the biological degradation of expanded polystyrene (EPS) and reported that EPS does not undergo short-term biodegradation in the presence of fungi and microorganisms and requires many years to decompose 5 . Biodegradable packaging composed of poly(lactic acid) (PLA) foam shows promise as an alternative, with a lower environmental impact than conventional EPS packaging.…”
Section: Introductionmentioning
confidence: 99%
“…The important bacteria in the biodegradation process include, interalia, Bacillus (capable of producing thick-walled endospores that are resistant to heat, radiation, and chemical disinfection), Pseudomonas, Klebsiella, Actinomycetes, Nocardia, Streptomyces, Thermoactinomycetes, Micromonospora, Mycobacterium, Rhodococcus, Flavobacterium, Comamonas, Escherichia, Azotobacter, and Alcaligenes (some of them can accumulate polymer up to 90% of their dry mass) [97,100,101]. Fungi that are active in the biodegradation process are Sporotrichum, Talaromyces, Phanerochaete, Ganoderma, Thermoascus, Thielavia, Paecilomyces, Thermomyces, Geotrichum, Cladosporium, Phlebia, Trametes, Candida, Penicillium, Chaetomium, and Aerobasidium [102,103].…”
Section: Biodegradationmentioning
confidence: 99%